Non-oxidized PTH (n-oxPTH) is associated with graft loss in kidney transplant recipients - Lu, YongPing; Zeng, Shufei; Chu, Chang; Hasan, Ahmed A.; Slowinski, Torsten; Yin, Liang-Hong; Krämer, Bernhard; Hocher, Berthold (Clinica chimica acta, 2020)
Elevated parathyroid hormone (PTH) concentrations were reported to be associated with chronic renal allograft failure. However, measurements of PTH are challenging, because PTH can occur either as non-oxidized (n-ox) or oxidized (ox) PTH. Only n-ox PTH is a PTH receptor agonist. The intact PTH (iPTH) concentrations measured routinely in clinical practice, however, equals non-oxidized PTH (n-oxPTH) plus oxidized PTH (oxPTH). In CKD patients, the majority of the circulating PTH is oxidized. We measured iPTH, oxPTH and n-oxPTH at study entry in 600 kidney transplant recipients (KTRs). They were followed for graft loss for 3 years. Graft loss was defined as need for initiation of renal replacement therapy. Thirty-eight patients had graft loss during the 3 years follow-up. OxPTH correlated very well with iPTH (R2 = 0.997, p < 0.0001), whereas the correlation between n-oxPTH and iPTH was much weaker (R2 = 0.762, p < 0.0001). Compared to KTRs without graft loss, KTRs with graft loss had significantly higher levels of iPTH, oxPTH, and n-oxPTH (p < 0.0001 in all cases). After adjusting for confounding factors in cox proportional hazards analysis, only n-oxPTH, but not oxPTH neither iPTH, was significantly associated with graft loss (Hazard ratio (HR): 1.02, 95% CI: 1.01-1.03, p = 1.84 × 10−3). The very close correlation between oxPTH and iPTH measurements suggests that conventional iPTH measurements most likely describe oxidative stress rather than PTH bioactivity. Only non-oxidized PTH but not oxidized PTH nor intact PTH is associated with graft loss in stable kidney transplant recipients.